General stability criterion of power electronic systems in the wind farm system - Miao, Linjing (2018)
In order to solve the problem which produced by the interaction between parallel inverters and long cables, or the different parameters of inverters in the wind farm system, we need to analyze the impact the cables and inverters has on the stability of the wind farm system, and then propose a general stability criterion which suitable for different occasions. According to the output waveforms and total harmonic distortions of the voltages and currents in the system, we can make the comparison between the single-phase inverter or parallel-connected inverter with short cable and long cable, and then conclude that different parameters of inverters and different length of cable are all play important roles in the stability of the system.